Special relativity a first encounter, 100 years since Einstein - Giulini, D. (Domenico), 1959- (Oxford University Press, 2005)
"Special relativity provides the foundations of our understanding of space and time. This book gives a modern introduction to the theory, and covers the most recent experimental developments"--Provided by publisher.